STUDY ON OBESITY AND OVERWEIGHT AMONG CHILDREN IN THE PRIMARY CYCLE AT INTERNATIONAL PLAN - Cojocaru Daniela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Prevention of obesity among children is a public health issue, and requires close monitoring of those with a tendency to gain weight. Most researchers believe that obesity, which has appeared since childhood and is maintained until adolescence, is much more difficult to treat. Obesity among children inevitably decreases life expectancy. The problem of overweight and excessive growth of obesity since childhood can be prevented or slowed down by implementing diversified programs, if society focuses more on the causes. There are many causes, some more crucial than others, but a balanced diet, combined with systematic physical activity, can prevent obesity and overweight in all children around the world. Next, I will present the studies done internationally regarding the presence of obesity and overweight in children aged 6-11 years.